Does location congruence matter? A field study on the effects of location-based advertising on perceived ad intrusiveness, relevance & value. (August 2017) - Hühn, Arief Ernst; Khan, Vassilis-Javed; Ketelaar, Paul; van 't Riet, Jonathan; Konig, Ruben; Rozendaal, Esther; Batalas, Nikolaos; Markopoulos, Panos
Abstract: We investigate the effect of location-congruent mobile messages on perceived intrusiveness, value, and relevance through a field experiment using the Experience Sampling Method (ESM). We developed a mobile application for undergraduate students, featuring campus news and information concerning class schedules. This application also included daily ads for the University restaurant, which were either location-(semi)congruent or location-incongruent. Immediately after viewing the ads the app presented a short questionnaire to the participants for a period of four weeks, thereby measuring their perceived intrusiveness, relevance and value of these ads. During these four weeks daily ads were sent to 40 students, resulting in 107 responses from 23 participants. The results show that our participants perceived location-(semi)congruent ads as significantly more valuable and relevant, whereas no significant results were found for perceived intrusiveness. By investigating LBA in a field-study based on ESM utilizing participants' own smartphone devices this study corroborates the presumed effects of location-(semi)congruency on marketing relevant ad perceptions. Highlights: Field experiment examines how individuals react to Location-Based Ads (LBAs). In situ data collection via ESM using a context-triggered sampling design. Location (semi)congruency has a positive influence on perceived relevance and value. LBA has no significant influence on perceived ad intrusiveness. Intra-individual variations are significant with all three dependent variables.